Sustainable land preparation for farmer-managed lowland agriculture in Indonesia - Sofiyuddin, M.; Suyanto, S.; Kadir, S.; Dewi, S. (Elsevier, 2021)
In almost all forms of agriculture and farming practice, land clearing is the initial step. In Indonesia, in general, the most cost effective means of clearing land is through the use of fire. However, this use of fire often results in uncontrolled outbreaks, particularly in lowland areas especially and during prolonged dry seasons. In recent years, these uncontrolled fire outbreaks have had a catastrophic environmental, social and economic impact. The Indonesian government has expressed a strong commitment to controlling these outbreaks, as demonstrated by a broad set of laws, regulations, decrees, guidelines, and directives to control and manage land and forest fire. However, despite these measures, the occurrence of widespread, high-intensity fire outbreaks is still unacceptably high. This study assessed land-clearing techniques associated with a low risk of fire outbreaks, comparing the costs associated with a range of these techniques. It then analyzed intervention options that would involve the adoption of these techniques by farmers. These low-risk techniques included: (i) zero-burning practices involving traditional machinery and farmer groups; (ii) zero-burning involving modern machinery and partnerships with government agencies/private enterprises; (iii) controlled burning; and (iv) the chemical removal of biomass using herbicides. The study finds that the costs for all four of these options are higher than with land-clearing techniques that use fire alone. However, it also showed that the cost implications for farmers could be mitigated by taking a more holistic view of farming practices as a system, rather than focusing only on land-clearing practices in isolation. It found that when land-clearing practices that involve low risks of fire outbreak are combined with good agricultural practices (GAP), farmers could still achieve higher levels of profitability and productivity than under a business as usual (BAU) scenario. The study produced scenarios involving BAU practices; land clearing without fire and with BAU practices; and land clearing without fire and with good agricultural practices (GAP) for four agricultural commodities (oil palm, cocoa, rubber, and paddy). It found that the return on land (NPV) in the case of the scenario involving land clearing without fire and with GAP was still higher than under the BAU scenario, except in the case of rubber, with which the NPV was higher in the scenario with modern machinery and GAP. The study concludes that a systems approach is necessary to effectively control fire outbreaks. Government programs should be designed and implemented on the basis of this systems approach with the involvement of a wide range of stakeholders, including through partnerships with the private sector operators, to effectively control the risk of fire outbreaks while at the same time supporting farmers' livelihoods by ensuring that they are enabled to generate higher levels of productivity and profitability from their land.